An Open-Label, Pilot Study of Daily Right Unilateral Ultrabrief Pulse Electroconvulsive Therapy. Issue 1 (March 2016) - Rasmussen, Keith G.; Johnson, Emily K.; Kung, Simon; Farrow, Stacy L.; Brown, Sarah K.; Govrik, Michael N.; Citronowicz, Ron I.
Abstract : Abstract: Right unilateral ultrabrief (RUL-UB) pulse width electroconvulsive therapy (ECT) has attracted much research attention recently due to its smaller effect on memory than is associated with other forms of ECT, such as bitemporal placement or unilateral standard pulse width. However, RUL-UB has demonstrated slower antidepressant efficacy in comparison to the other techniques. One method to enhance the speed of response to RUL-UB ECT is administration of 5 times a week (termed "daily") treatments as opposed to the more standard twice or thrice weekly schedule. In this open label study, we treated 20 depressed patients with daily RUL-UB treatments for up to 2 weeks (ie, 10 treatments) using standardized assessments of depression and retrograde amnesia. Response and remission rates were commensurate with those reported in other recent studies using this technique with twice or thrice weekly treatment frequencies, and there was no clinically significant effect on retrograde memory function. We conclude that daily administration of RUL-UB ECT may shorten the duration of the course of ECT treatments without compromising cognition. A randomized trial comparing this technique to a thrice weekly schedule of RUL-UB treatments is indicated.